2007
DOI: 10.1037/0021-843x.116.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Stress-response-dampening effects of alcohol: Attention as a mediator and moderator.

Abstract: The present study sought to characterize alcohol's stress-response-dampening (SRD) effects on multiple measures of stress and whether these effects are mediated by reductions in sustained attention and, further, whether baseline levels of sustained attention moderate SRD. One hundred six men consumed either an alcohol (0.70 g/kg) or a placebo beverage prior to learning that they would deliver a self-disclosing speech. Structural equation models controlling for multiple baseline periods indicated that alcohol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
94
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 76 publications
8
94
1
3
Order By: Relevance
“…For instance, some researchers have suggested that alcohol leads individuals to focus on the most salient aspects of a situation by impairing their ability to divide attention, rather than by narrowing their attentional focus (Curtin, Lang, Patrick, & Stritzke, 1998;Curtin, Patrick, Lang, Cacioppo, & Bierbaumer, 2001). Other researchers have emphasized the role of impaired sustained attention in explaining alcohol-myopic effects (Sher, Bartholow, Peuser, Erickson, & Wood, 2007). Further research is needed to investigate the precise mechanisms for the effect of alcohol on commitment.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For instance, some researchers have suggested that alcohol leads individuals to focus on the most salient aspects of a situation by impairing their ability to divide attention, rather than by narrowing their attentional focus (Curtin, Lang, Patrick, & Stritzke, 1998;Curtin, Patrick, Lang, Cacioppo, & Bierbaumer, 2001). Other researchers have emphasized the role of impaired sustained attention in explaining alcohol-myopic effects (Sher, Bartholow, Peuser, Erickson, & Wood, 2007). Further research is needed to investigate the precise mechanisms for the effect of alcohol on commitment.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Assessing the physiological effects of short-term psychological stressors is more problematic, and is generally attempted by measurement of physical characteristics including respiration rate and skin conductance [11,12] in addition to heart rate, blood pressure and body temperature [5,6,7,8]. All are subject to considerable biological variation, introducing uncertainty to comparison between individuals and populations.…”
Section: Introductionmentioning
confidence: 99%
“…The central amygdala (CeA), a structure mediating emotional behaviors such as anxiety and fear, is implicated as a critical brain region in stress-related drinking, given that the anxiolytic effects of ethanol motivate drinking as self-medication (Sher et al, 2007). In addition, recent studies suggested that the CeA, as part of the extended amygdala, plays a critical role in the positive motivational effect of ethanol (Koob et al, 1998;McBride, 2002).…”
mentioning
confidence: 99%